Selfies : why we love (and hate) them - Tiidenberg, Katrin (Bingley : Emerald Publishing Limited, 2018)
This book presents a rich and nuanced analysis of selfie culture. It shows how selfies gain their meanings, illustrates different selfie practices, explores how selfies make us feel and why they have the power to make us feel anything, and unpacks how selfie practices and selfie related norms have changed or might change in the future.
To Understand the Media Discourse that Links Selfies to NarcissismTo Understand the Linguistic Productivity of the Selfie Word; Recommended Other Readings (Not Referenced in Text); To Understand Social Media; To Understand Social Media Affordances; To Understand Networked Visuality and Its History; To Understand Machine Vision; To Understand Post-Digital; If You're Interested in Practice Theory; Index.
Includes bibliographical references and index.
Vendor-supplied metadata.
Master record variable field(s) change: 072
Keywords: Online social networks; Social media -- Research; Digital images -- Social aspects; Self-portraits -- Social aspects; PSYCHOLOGY -- Social Psychology; Popular culture; Online social networks; Electronic books